Robot-Assisted Total Hip Arthroplasty for Arthrodesed Hips - Chai W; Kong X; Yang M; Puah KL; Tang P; Chen J (Dove Medical Press, 2020)
Wei Chai,1 Xiangpeng Kong,1 Minzhi Yang,1,2 Ken Lee Puah,3 Peifu Tang,1 Jiying Chen1 1Department of Orthopedics, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Medical College, Nankai University, Tianjin, People’s Republic of China; 3Department of Orthopedic Surgery, Singapore General Hospital, SingaporeCorrespondence: Jiying Chen; Peifu Tang Tel +8610-66938404; +8610-66938304Email chenjiyingjoint@sina.com; pftang301@126.comBackground: Conversion of arthrodesed hips to total hip arthroplasty (THA) remains technically demanding. This study aims to evaluate the safety and efficacy of robot-assisted THA in arthrodesed hips.Methods: We retrospectively analyzed 45 ankylosing spondylitis patients with hip arthrodesis in the Chinese PLA General Hospital between August 2018 and August 2019. All surgeries were carried out by one single surgeon. The patients were followed at 3 months after surgery. Gender, body mass index, angle of hip arthrodesis, operating time, intraoperative fluoroscopic times, postoperative length of hospitalization, cup positioning, postoperative leg length discrepancy, offset discrepancy, intraoperative and postoperative complications, and postoperative Harris Hip Score were collected for all patients.Results: Twenty-two patients (35 hips) who underwent robot-assisted THA and 23 patients (37 hips) who underwent manual THA were enrolled in this study. There were no significant differences in demographics and arthrodesed angles between the two groups. The fluoroscopic times during manual THA were significantly higher than those during robot-assisted THA (2.16± 1.61 vs 0.47± 0.61, respectively, p=0.000). In the robotic group, the percentage of acetabular cups within the safe zone was significantly greater than in the manual group (94.29% vs 67.56%, respectively, p=0.042). For manual THA, the anteversions were significantly different between the left and right sides (21.14± 7.86 vs 16.00± 6.32, respectively, p=0.042); however, no such significant difference was found in robot-assisted THA.Conclusion: Compared with manual THA for arthrodesed hips, robot-assisted THA had significant advantages in improving the frequency of achieving cup positioning within the target zone with diminished radiation dose and no increase in operating time.Keywords: total hip arthroplasty, robot-assisted surgery, cup positioning, hip arthrodesis